Applying Marketing Mix (4Ps) to Enhance the Adherence of Asthmatics in China - ZHOU, HAITAO (2017)
This project has first tried apply the knowledge of social marketing to improving the adherence of asthmatics in China. The researcher has found 14 participants who are voluntary to take part in this project through the personal contact. Ages of all participants ranged from 20 to 40years and all participants provided the confirmed consent. In the main body, the author introduced and explained how the social marketing influence the patient adherence. In addition, the Health Beliefs Model was applied to this research and each component was associated with the research results. Finally, the researcher concluded social marketing knowledge would be an alternative method to increase the adherence of asthmatics in this case.